Efektivitas Latihan Variatif terhadap Peningkatan Teknik Servis Atas dalam Ekstrakurikuler Bola Voli SMAN 17 Garut - Abdurahman, Muslim; Sonjaya, Azhar Ramadhana; Arifin, Z (Universitas Hamzanwadi, 2025)
This study aims to analyze the effectiveness of varied exercises in improving volleyball top serve skills. The main problem in this study is the low level of accuracy, strength, and consistency of the upper serve movement caused by monotonous training methods. This study used a quantitative approach with a one-group pretest-posttest pre-experiment design. The population of this study were all students who participated in volleyball extracurricular activities at SMAN 17 Garut, with a sample of 20 male students using non-probability sampling technique. The instrument used in data collection is the upper serve skill test. The data analysis technique used is the descriptive statistics test and paired sample t-test. The results of the average value of prettes amounted to 19.80 and posttes 32.30. with a selisia of 12.5. The total value of student serves ranged from 15 to 23 with an average of about 19.6. After being given varied exercises, the scores on the final test (posttest) increased to range from 30 to 35 with an average of about 32.2. This increase reflects the improvement of students' abilities in terms of accuracy, strength, and consistency of the upper serve. Thus, varied exercises can be used as an effective strategy in learning volleyball, especially to optimize the upper serve technique at the high school level.